Household biocide use and personal safety practices among rural population in South India: A community-based study - Karthik Balajee Laksham; Vinothkumar Kalidoss; Parthibane Sivanantham; Perumal Murthy Sambath; Manoj Kumar Arunachalam; Palanivel Chinnakali (Nofer Institute of Occupational Medicine, 2016)
Background: Household pesticides (biocides) are widely used for the purpose of controlling vector-borne diseases. Exposure to biocides causes various health hazards in human beings. Prevalence of biocide use, storage methods, and personal protection measures while handling biocides are not known among rural households in South India. Material and Methods: A communitybased cross-sectional study was conducted among 416 households in rural Puducherry (union territory). Information on household biocide use, frequency of use, storage and personal safety practices were captured using pretested questionnaire. Continuous variables like age are summarized by mean and standard deviation. Categorical variables like gender, education, a type of a house, biocide usage and related handling practices are summarized as proportions. Results: Majority (85%) of the households reported presence of at least 1 biocide. Mosquito liquidizer was the most commonly used biocide (45%) followed by mosquito coil (31%), ant powder (30%) and ant chalk (20%). Protection measures against the majority of used biocides were used only in few households and no personal protection measures were used while handling mosquito coil, mat, ant chalk and rat powder. Conclusions: The prevalence of household biocide use is high in the study setting. Storage, handling and post handling practices were not sufficient to protect health. Med Pr 2016;67(5):599-604